Design and performance analysis of the thrust gas bearing with single orifice for helium turbine. Issue 1 (1st May 2022) - Li, S S; Fu, B; Zhang, Q Y; Chen, S X
Abstract: Thrust bearing is an important component for the stability of helium turbo-expander, and is a critical part to ensure the stable operation of helium refrigerator. A thrust bearing with single orifice is designed at the end of the fan brake for a home-made 500W@4.5K helium turbine. This design optimizes the mechanical structure of the rotor and improves the overall stability of the helium turbine. To increase the axial capacity, the static and dynamic calculation model of this thrust bearing is established to analyse the performance. This paper describes the variation curve of parameters and studies the influence of temperature on bearing performance by numerical simulation method. The analysis as more simple and efficient method is used to obtain the important parameters of this thrust gas bearing with single orifice, which meets the demand of the whole engineering design for helium turbine expander.